MENINGITIS BAKTERIAL STREPTOCOCCUS SUIS DENGAN TULI SENSORINEURAL BILATERAL - Ni Made Susilawathi,* Ni Made Adi Tarini,** Anak Agung Raka Sudewi * (NEURONA, 2016)
MENINGITIS CAUSED BY STREPTOCOCCUS SUIS S SUIS A ZOONOSIS DISEASE THAT CAN BE TRANSMITTED BY PIGS RARELY REPORTED IN INDONESIA THE COMPLICATION OF SENSORINEURAL HEARING LOSS DEVELOPS DURING THE ACUTE STAGE OF MENINGITIS WE REPORT A CASE OF S SUIS MENINGITIS WITH HEARING LOSS